Do Longer Dry Spells Associated With Warmer Years Compound the Stress on Global Water Resources?. Issue 2 (16th February 2022) - Hettiarachchi, Suresh; Wasko, Conrad; Sharma, Ashish
Abstract: Availability of water resources is significantly affected by changes in seasonal rainfall, with water often in short supply when most needed. The majority of current research focuses on the impacts of multiyear drought, using monthly or annual average rainfall to investigate impacts to water resources. Here, we use daily rainfall to evaluate changes in dry spells lengths, defined as the continuous number of days without rain, and investigate how these changes may impart stresses on water resources in warmer summer seasons globally. We use over 100 years of precipitation and temperature data across the world, arranged into warm and cold groups of years on the basis of mean summer temperature. These warm and cold groups are then compared to demonstrate an overwhelming tendency for warmer summers to contain longer dry spells globally. This difference in dry spell length in warmer summer seasons is argued to have far reaching ramifications in warmer summers. For some of the largest cities in the world, vulnerability of water resources, which is a measure of the magnitude or severity of the water availability deficit, is shown to be on average 30% higher due to longer seasonal dry spells in warmer summers. Such an impact points to a need to reassess water resources plans and policies to include the impacts of seasonal dry spells, especially relating to large urban populations around the world. Plain Language Summary: Lack of water is a serious threat to our environment, eco systems, and to human life. Availability of water is projected to get worse with decreases to average rainfall resulting from climate change. Here, we illustrate that periods of continuous days without rain, or dry spells, can also cause damage to the environment and can also result in water shortages for human consumption. This aspect of the length of seasonal dry spells is not usually captured in current projection and modeling. As an alternative to global circulation model results of rainfall, we use historic data classified by mean summer temperature to collect the hottest and coldest years and as an indicator of changes caused by a warming climate. We show that longer dry spells are associated with warmer years globally and that these dry spells do contribute to increasing on the stress on water resources around the world. Key Points: Longer periods of continuous dry days in warmer summers, globally Increases stress on water resources due to longer dry spells all around the world Seasonal dry spells also should be considered along with long‐term droughts